Study of the biogas potential generated from residue: peanut shells - Santos, Cristiano Vieira dos [UNESP]; Lourenzani, Ana Elisa Bressan Smith [UNESP]; Neto, Mario Mollo [UNESP]; Lopes, Leonardo Alexandre [UNESP]; Santos, Paulo Sergio Barbosa dos [UNESP] (Associacao Brasileira De Engenharia Sanitaria E Ambiental, 2021)
The increase in agricultural production generates a large volume of waste, which may lead to concerns about its proper destination. The main economic activity in Herculandia City, Western region of Sao Paulo State, Brazil, is the production and processing of peanuts. In this process, a large volume of peanut shells is generated. Following the current movement of using waste for energy purposes, in compliance with what was established by the Sustainable Development Goals (SDGs), this work aimed to carry out a study on the biogas potential generated from peanut shells. To this end, a low-cost biodigester prototype was built, which, over a period of 108 days, produced biogas and biofertilizer. The results showed that there was production of biogas from peanut waste; however, the volume produced did not provide savings in electricity costs when compared to the production of biogas from animal waste. Nevertheless, the work demonstrated the importance of providing solutions to the disposal of peanut shells, effectively mitigating future environmental problems, and serving as an alternative for generating sustainable and low-cost energy, especially for small producers.
Keywords: biogas; peanut shells; electricity; waste